Diagnosis of sepsis‐induced disseminated intravascular coagulation and coagulopathy. Issue 3 (1st April 2019) - Iba, Toshiaki; Umemura, Yutaka; Watanabe, Eizo; Wada, Takeshi; Hayashida, Kei; Kushimoto, Shigeki; ,
Abstract : Disseminated intravascular coagulation (DIC) is a frequent complication in sepsis. Once patients develop DIC, the mortality rate increases significantly. Moreover, recent studies have suggested that coagulation disorder plays a significant role in the development of organ dysfunction in sepsis. Thus, the early detection of DIC is vital in sepsis care, and the Japanese Association for Acute Medicine established a set of original diagnostic criteria in 2006 (JAAM DIC). Since then, the usefulness of the JAAM DIC has been repeatedly reported, and these criteria have been widely adopted in emergency and critical care settings in Japan. Different criteria have also been released by the International Society on Thrombosis and Haemostasis (ISTH overt‐DIC), and the latter criteria are presently considered to be the international standard. Compared with the JAAM DIC, the ISTH overt‐DIC criteria are stricter and the timing of diagnosis is later. This discrepancy is because of conceptual differences. As many physicians think sepsis‐associated DIC is the target of anticoagulant therapies in Japan, the JAAM DIC criteria were designed to allow the early initiation of treatment. As other countries do not provide DIC‐specific treatments, early diagnosis is not necessary, and this situation has led to a significant gap. However, as overt‐DIC is a late‐phase coagulation disorder, a need for early detection has been advocated, and members of the ISTH have recently proposed the category of sepsis‐induced coagulopathy. In this review, we introduce the strengths and weaknesses of the major criteria including JAAM‐DIC, ISTH overt‐DIC, sepsis‐induced coagulopathy, and Japanese Society on Thrombosis and Haemostasis‐DIC. Abstract : The International Society on Thrombosis and Haemostasis (ISTH) criteria for overt disseminated intravascular coagulation (DIC) are recognized as the global standard, whereas DIC criteria set by the Japanese Association for Acute Medicine are the most popularly used in Japan. To harmonize the standard, new criteria are proposed by ISTH.